ASSESSING OF ROCKFALL RISKS (CASE STUDY: KLÖCH, AUSTRIA) - Sandyavitri, Ari; Preh, Alexander; Tohom, Frans (FSTPT Indonesia, 2015)
Rockfall cases are a natural and dynamic geologic process, commonly occur within mountainous areas near by the cliffs undercut by human for developing building or highway. This paper aims are to; (i) identify parameters of slope surface, and (ii) simulates rockfall process. Case study of slope was taken in the quarry at the Kloch, Austria. This paper revealed 7 (seven) slope surface parameters for this slope, including; dynamic and static friction angles were 350, normal and tangential damping were 0.2 and 0.95, rolling resistance 0.2 to 0.3, amplitude of roughness 0, and frequency of roughness 1. These results were than treated as an input data in simulating the rockfall. Based on the simulation, it was identified that within the 15 m of the Kloch height, the rocfall would yield the average of kinetic energy of 240 kJ, and 0.5 m of bounce height. Hence, in order to reduce rockfall risk to road way close to the cliff toe area, it is recommended to extend road shoulder at 5-10 meters from the slope or construct an appropriate rockfall barrier that is in capable to restrain energy kinetic of 250 kJ and the height of barrier minimum 1 m.